KAYANGAN: lightweight authentication and key agreement scheme using HPKE for 6G Non-Terrestrial Networks - Khalid, Haqi; Hashim, Shaiful Jahari; Abdulsaheb, Jaafar Ahmed (Ain Shams University, 2025)
The evolution of sixth-generation (6G) communication requires secure and efficient mechanisms for Non-Terrestrial Networks (NTNs), where high mobility, latency, and exposure to security threats pose critical challenges. This paper presents KAYANGAN, a lightweight key agreement scheme based on Hybrid Public Key Encryption (HPKE). The scheme ensures mutual authentication, session key freshness, and secure handovers in dynamic NTN environments. Its security is formally validated through BAN logic and the AVISPA tool, confirming resistance to replay, impersonation, and man-in-the-middle attacks. Performance evaluation using OMNeT++, VEINS, and SUMO shows clear advantages over existing protocols, including 20.8 % lower end-to-end delay, 13 % higher throughput, 24 % lower energy consumption, 16.1 % lower computation cost, and 23.3 % reduced communication overhead. These results confirm that KAYANGAN is a practical and efficient solution for securing resource-constrained NTN applications such as UAV networks and satellite-based IoT.”.